84.9k views
0 votes
What is the solution to the following system of equations?

x-3y=6
2x + 2y = 4
(-1,3)
(3,-1)
(1, -3)
(-3,1)

1 Answer

2 votes

Answer:

(b) (3,-1)

Explanation:

One can determine the correct answer by checking to see if it satisfies the equations.

Checking

The first equation can be rewritten to ...

x = 6 +3y . . . . . . . add 3y to both sides

This makes it easier to check answer choices:

a) -1 = 6 +3(3) . . . . no

b) 3 = 6 +3(-1) . . . . yes . . . . . (3, -1) is the solution

c) 1 = 6 +3(-3) . . . . no

d) -3 = 6 +3(1) . . . . no

__

Additional comment

We can further convince ourselves this is the correct choice by seeing if it satisfies the second equation:

2x +2y = 4 . . . for (x, y) = (3, -1)

2(3) +2(-1) = 4 . . . . yes

User BitAccesser
by
5.3k points